In Vitro Immune Response of Mononuclear Cells to Multidrug-Resistant Escherichia coli - Berta Cuyàs; Elisabet Cantó; Elisabet Sanchez-Ardid; Elisenda Miró; Edilmar Alvarado-Tapias; Eva Román; Maria Poca; Ferran Navarro; Andreu Ferrero-Gregori; Maria Àngels Escorsell; Silvia Vidal; German Soriano (Microorganisms)
Infections caused by multidrug-resistant organisms (MDRO) are linked to poor outcomes, particularly in patients with cirrhosis. The underlying mechanisms are not fully understood and may involve a different immune response against MDRO. This study aimed to compare the in vitro immune response between multidrug-resistant (MDR) Escherichia coli and antibiotic-susceptible E. coli strains. Surface protein extract and DNA extract were obtained from MDR E. coli (n = 6) and antibiotic-susceptible E. coli (n = 6) strains isolated from infected patients with cirrhosis. The extracts were used to stimulate in vitro peripheral blood mononuclear cells from healthy donors. After 48 h, cytokine levels (IFN-γ, IL-1β, IL-10, IL-12p70, MCP-1, IL-8, IL-6, MIP-1α, and MIP-1β) were measured. We observed no significant differences in cytokine production between MDR and susceptible strains. However, we identified notable interindividual variability in cytokine production for most of the cytokines studied. Only IFN-γ and IL-6 in surface extract and MCP-1 in DNA extract showed similar levels across all donors. We conclude that the cytokine profiles induced by MDR E. coli in vitro were similar to those in susceptible strains. These findings suggest that the poor prognosis associated with MDR E. coli infections is not due to a differential immune response but rather to other factors.